EDUCATION AND UNEMPLOYMENT EFFECTS ON POVERTY IN SOUTHEAST SULAWESI - Puspa Dewangga; Zainuddin Saenong; Muhammad Syahrul Mubarak; La Ode Muhammad Iksan Yusuf (JISEF : Journal Of International Sharia Economics And Financial, 2026)
This study analyzes the effects of education and unemployment on poverty in Southeast Sulawesi during 2010–2025. The study uses a quantitative approach with annual time series data obtained from the Central Statistics Agency (BPS). The variables used include the poverty rate, average years of schooling, and the open unemployment rate. The analytical method applied is the Autoregressive Distributed Lag (ARDL) model to examine short-run and long-run relationships among variables. The results indicate the existence of a long-run relationship among education, unemployment, and poverty. Education has a significant negative effect on poverty in the long run, indicating that higher educational attainment contributes to poverty reduction. Meanwhile, unemployment has a positive but statistically insignificant effect on poverty. In the short run, lagged unemployment changes significantly affect poverty dynamics. Diagnostic and stability tests confirm that the ARDL-ECM model is statistically reliable and stable. These findings suggest that poverty reduction in Southeast Sulawesi should prioritize improving educational quality and human capital development, alongside more inclusive labor market policies.